2021
DOI: 10.1016/j.diagmicrobio.2021.115519
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative effects of thermal treatment of naso-oropharyngeal samples before cobas SARS-CoV-2 testing

Abstract: To improve laboratory safety we thermally treated naso-oropharyngeal samples before testing with the cobas SARS-CoV-2 assay. This study aimed to determine if thermal treatment significantly affects the qualitative detection of SARS-CoV-2 and the quantitative measurement of cobas SARS-CoV-2 ORF1a and E-gene target copy number using an in-house quantitative method. A collection of positive ( n= 238) and negative samples ( n= 196) was tested in parallel comparing ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The conventional VTM reagent allows viruses to remain viable; the resulting high risk of infection during transportation and detection leads to increased costs because of the need for greater protection. The use of heat to inactivate viruses in clinical samples can affect the stability of viral nucleic acids, particularly RNA 22 . Sampling solutions that contain guanidine salts can effectively inactivate viruses, but a nucleic acid extraction step is required for sample detection.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional VTM reagent allows viruses to remain viable; the resulting high risk of infection during transportation and detection leads to increased costs because of the need for greater protection. The use of heat to inactivate viruses in clinical samples can affect the stability of viral nucleic acids, particularly RNA 22 . Sampling solutions that contain guanidine salts can effectively inactivate viruses, but a nucleic acid extraction step is required for sample detection.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization experiments have shown that high temperature and short durations (95 to 98°C for 5 to 15 min) improve (reduce) C q values compared to lower temperature and longer durations (60°C for 30 min) ( 9 ). Heat inactivation prior to testing with extraction-based methods also reduces the sensitivity of SARS-CoV-2 RNA detection ( 4 , 18 , 19 ). Other investigators have shown the addition of proteinase K (55°C for 15 min) followed by heat treatment also improves C q values up to three cycles compared to heat treatment alone ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the early stages of the pandemic, samples were tested using the cobas SARS-CoV-2 assay (Roche catalog number 09175431190) as the primary testing method. Thermal pretreatment of the sample was performed before cobas testing ( 3 , 4 ). We implemented the PlexPCR SARS-CoV-2 assay (SpeeDx catalog number 1301384) in September 2020 as an additional testing method to increase testing capacity ( 5 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation